PROMOSI PENJUALAN dan MINAT BELI (Studi Korelasional Antara Promosi Penjualan Pakaian Wanita dan Minat Beli Siswi SMA Negeri I Medan) - Isabella Deliana Simamora (FLOW, 2012)
This paper describes an correlational study between women's clothing sales promotion on facebook with interest in buying students SMA Negeri I Medan. The purpose of this study was to determine the extent of the relationship between women's clothing sales promotions on facebook and buying interest SMA Negeri I Medan. Dalam penelitian ini menunjukkan adanya hubungan promosi penjualan dan minat beli siswi di SMA Negeri I Medan.   Keywords: Promosi Penjualan dan Minat Beli